Coordinated Mekong Ministerial Initiative against Trafficking (COMMIT) to Combat Human Trafficking in Thailand - Andien Dewi Aulia Zahra; Taufik Taufik; Shylvia Windary (UNIDA Gontor, 2025)
The phenomenon of intra-regional migration has occurred since 1980 in Southeast Asia and continues to increase. One of them is in the sub-region known as the Greater Mekong Subregion (GMS). GMS countries including China (Yunan Province and Guangxi Autonomous Region), Lao People's Democratic Republic (Lao PDR), Cambodia, Myanmar, Thailand, and Vietnam, have different economic conditions. Thailand is a country with the strongest economy, thus attracting migrants to work in Thailand, especially migrants from Cambodia, Lao PDR, and Myanmar. This mobility has opened up opportunities for human trafficking, so the six countries agreed to a memorandum of understanding which continued with the formation of the Coordinated Mekong Ministerial Initiative Against Trafficking (COMMIT) and issued the Subregional Plan of Action (SPA). This study aims to determine the implementation of SPA IV carried out by Thailand in the period 2018 - 2022 along with its obstacles. As a result, in implementing the Subregional Plan of Action IV COMMIT, Thailand has focused more on measures to prevent human trafficking, protect victims, and prosecute perpetrators. However, implementation has also encountered obstacles due to the COVID-19 pandemic